Effects of perinatal exposure to diazepam on the development of sexual behavior and neuroendocrine functions in male rats. - Arif Siddiqui (Al Ameen Journal of Medical Sciences, 2008)
Developmental exposure with diazepam when coinciding with the ontogenesis of its receptors may be crucial for the induction of long-term functional disturbances in the rat brain. To investigate the possibility of intervention in the sexually dimorphic behavior of reproduction and the under lying morphological and hormonal basis the time-mated female rats were treated with 2.5 mg/kg, 5 mg/kg and 10 mg/kg, i.p.(n = 6-8) separately. Treatment was continued from gestation day 15 till delivery and further continued to neonates 5 days, postnatally. Control group (n= 5-8) given saline also followed the same treatment protocol. Sexual behavior in the male offspring at adulthood born to diazepam-exposed rats was enhanced, both in dose-dependent and time-dependent manner (p<0.01). Accordingly plasma LH and testosterone concentration both in plasma and testis was also influenced. Compared to controls treated animals also showed complete abolition of spermatogenesis and drastically reduced testicular steroidogenesis. Our findings, thus support the hypothesis that like psychoactive drugs benzodiazepines sedatives that crosses the blood brain barrier during the critical period of brain sexual differentiation offer serious risk of abnormal post-pubertal reproductive functions in the male rat.